Key quality aspect: a fundamental step for quality improvement in a resource-poor setting - Tin, Tin Su; Sax, Sylvia (SAGE Publications, 2009)
The objective of the study is to identify user's perception of key quality aspects of the hospital and its influence on willingness to pay. The study was conducted in 2001 in Dhading District Hospital, Nepal. This was a descriptive, cross-sectional study design using quantitative and qualitative methods: questionnaire exit interview and focus group discussions with inpatients and outpatients, focus group discussion with service providers, and key informant interviews. The research identified attitude, technical and interpersonal skills of health personnel, availability of drugs and services as important quality aspects to be improved. Users were motivated to use this hospital and were ready to pay if they received proper treatment from skilled and communicative staff. This study highlights the importance of identifying the quality factors important to service users as a first step in improving quality. For the users within this study, this meant improving attitude, interpersonal skills, and technical skills of service personnel.